Voice & speaking skills for dummies - Apps, Judy (--For dummies., 2012)
Find your voice, and communicate with confidenceEver wondered why nobody hears you in meetings, or wished people would take you more seriously? Or maybe you're unhappy with your accent, or you feel insecure about your high-pitched or monotonous voice? Voice and Speaking Skills For Dummies will help you to discover the power of your voice, understand how it works, and use your voice like a professional whether in meetings, addressing an audience, or standing in front of a classroom. Take a deep breath, relax those vocal cords, and make your speech sparkle!We're not all planning to become politi.